Innovative Maritime Learning through Virtual Tour and Augmented Reality with an Interactive Approach for Competency Enhancement - Dimas Pristovani Riananda; Afif Zuhri Arfianto; Isa Rachman; Muhammad Izzul Haj; Aminatus Sa'diyah; Widya Emilia Primaningtyas (JINoP (Jurnal Inovasi Pembelajaran), 2025)
This study explores the use of Virtual Tour and Augmented Reality (AR) technologies in maritime education, aiming to enhance student competencies through interactive learning experiences. The research employed a mixed-method approach, combining quantitative surveys and qualitative interviews to assess the platform's effectiveness. Data were collected from 60 students, with results showing that 80% of participants found AR highly effective for understanding ship systems, and 75% reported increased motivation to learn. A moderate negative correlation (-0.54) was identified between the Effectiveness of AR Technology and Motivation to Learn, suggesting that while AR simplifies complex concepts, it may reduce intrinsic motivation. Furthermore, technical difficulties impacted perceived effectiveness, with students experiencing fewer technical issues rating AR higher (4.19) than those encountering difficulties (3.93). Interestingly, students facing technical challenges reported higher motivation to learn (4.21) than those without difficulties (3.44), indicating that overcoming obstacles may enhance engagement. This study underscores the importance of optimising AR platforms for device compatibility and user support to maximise their educational potential. The findings suggest that while AR technology significantly improves understanding, attention must be given to balancing technical efficiency with user motivation